Membrane display and functional analysis of juxtacrine ligand-receptor signaling. (October 2015) - Nair, Pradeep M.; Ngu, Hai; Torres, Eric; Marsters, Scot; Lawrence, David A.; Stephan, Jean-Philippe; Komuves, Laszlo; Ashkenazi, Avi
We developed a strategy for identifying modulators of juxtacrine signaling, triggered by a cell-surface ligand displayed on synthetic lipid bilayers, via cognate receptors on apposed cells. Using readouts for receptor lateral transport and intracellular signaling, we screened a small interfering RNA (siRNA) library and identified specific receptor tyrosine kinases (RTKs) that directly or indirectly modulate apoptosis signaling by a model death ligand through its cognate death receptors. This approach may be broadly useful for studying juxtacrine cell–cell signaling systems.